METHODOLOGY FOR DEVELOPING DIVERGENT THINKING OF PRIMARY SCHOOL PUPILS - Xo’jamberdiyeva Sarvinoz Keldiyarovna (Journals Park Publishing, 2023)
This article talks about the formation of divergent thinking of primary education students.
Keywords: divergent, intellectual, concept, identification, Attention, Perception, process of associations, thinking.